Uso de internet no Brasil: uma análise baseada na Teoria de Resposta ao Item (TRI) - Santos, Aline Rodrigues (2012)
This dissertation aims to identify how is the use of the Internet by Brazilian considering the dimensions: electronic government, entertainment, information, communication, education, commerce, and analyzing wich items are better discriminators of the dimension and build an indicator of the types of precedence use. The source of data is secondary and provided by the study center on the CETIC ICT Households 2009. And through the statistical technique of Item Response Theory (IRT) of the sample every American will receive a score related to their responses to the items of the scale. This paper presents results that allow us to explain issues related to Internet use for Brazilians. For some dimensions are grouped items to display the dimension broken down into groups. For the dimensions of Electronic Commerce and Electronic Government concluded that the items of its dimensions do not discriminate against groups of Brazilians with their use, because the characteristic curve of the item, each item discriminates against the Brazilians in the same dimension in the same way. As for Communication, Education, and Recreation Information is broken down by groups of items most likely to use by the Brazilian and uses less likely.